2021
DOI: 10.1136/bmj.n1637
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Innova SARS-CoV-2 antigen rapid lateral flow test in the Liverpool asymptomatic testing pilot: population based cohort study

Abstract: Objective To assess the performance of the SARS-CoV-2 antigen rapid lateral flow test (LFT) versus polymerase chain reaction testing in the asymptomatic general population attending testing centres. Design Observational cohort study. Setting Community LFT pilot at covid-19 testing sites in Liverpool, UK. Participants 5869 asymptomatic adults (≥18 years) voluntari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 28 publications
3
108
0
2
Order By: Relevance
“…For example, the Innova SARS-CoV-2 antigen rapid lateral flow test that is widely used in England has high sensitivity on samples with higher viral load (91% for samples with Ct < 18.3, 69% for samples with Ct < 24.4) and poor sensitivity otherwise (9.7% for samples with Ct < 24.4). 41 Our model for antigen test matches the sensitivity of this test for moderate to high viral loads as we generally expect for carriers with the delta variant, but may not represent real-world scenarios for other antigen tests. In a low prevalence situation, both PCR and antigen testing can yield a substantial number of false positive results.…”
Section: Discussionmentioning
confidence: 86%
“…For example, the Innova SARS-CoV-2 antigen rapid lateral flow test that is widely used in England has high sensitivity on samples with higher viral load (91% for samples with Ct < 18.3, 69% for samples with Ct < 24.4) and poor sensitivity otherwise (9.7% for samples with Ct < 24.4). 41 Our model for antigen test matches the sensitivity of this test for moderate to high viral loads as we generally expect for carriers with the delta variant, but may not represent real-world scenarios for other antigen tests. In a low prevalence situation, both PCR and antigen testing can yield a substantial number of false positive results.…”
Section: Discussionmentioning
confidence: 86%
“…Conversely, though lateral flow antigen testing (LFT) for SARS-CoV-2 has been widely commercialized for its use in airports, pharmacies, schools and universities, it has been questioned for its degree of sensitivity, which has shown not to meet the minimal performance requirements of WHO and ECDC [22,23]. For instance, in the Liverpool pilot, LFT is likely to detect around a third and, at most, half of the PCR positive cases [24].…”
Section: Discussionmentioning
confidence: 99%
“…The interim results of the national pilot were reported in December and showed that the rapid test kits missed over half of cases 2. The full evaluation of the test’s performance, published in The BMJ ,3 said that when the accuracy of LFTs was assessed against PCR results, the overall sensitivity of the Innova test was 40%. The specificity was found to be 99.9%, the positive predictive value is 90.3%, and the negative predictive value is 99.2%.…”
Section: Infections Preventedmentioning
confidence: 99%